Ontology Model of a Robotics Agents Community - Salinas-Silva, R (Agora University, 2011)
This paper presents an Ontology Model of necessities and decisions for a cooperative community of heterogeneous robotic agents. Based on an ant community, it defines the characteristics of a collaborative and cooperative community of robots, using multi agent theory where each robot shares information with others robots in the community, to accomplish a common objective. © 2006-2011 by CCC Publications.